Perancangan dan Pengembangan Aplikasi E-commerce pada Catering Anugrah - Sudirman, Bagus; Tristianti, Mawada (MEANS (Media Informasi Analisa dan Sistem), 2022)
Bank reconciliation is one of the ways that companies do as a form of internal company control. CV Lisa Pratama in the company's internal control has not carried out a bank reconciliation. The methods used in this research are interviews, observation and literature, while the bank reconciliation method is used as a method of solving existing problems, the research method uses the research and development method of R&D (Research and Development) and the system development method uses the SDLC (System Development Life Cycle) method. . For internal control, the company uses bank reconciliation. Based on the evaluation, it can be concluded that the CV. Lisa Pratama has not conducted bank reconciliation every month. Bank reconciliation aims to match company balances with bank checking accounts so that the company knows the causes of differences in balances such as bank interest income transactions and bank administration fees which are only known to the bank which is not yet known by the company and vice versa. The benefit of reconciliation for the company is as an internal control for bank cash receipts and payments.